Zapisz w jak najprostszej postaci:
a) (10x+2y)/2 =
b) 6 • (x + 1) + 3 • (x – 1) =
c) 6 • (x + 1) - 3 • (x – 1) =
d) (x + 4)² =
e) (2x + 3y) • (3x – 2y) =
f) (x – 5) • (x + 5) – 2 • (x² + 1) =
g) (x – 3y) • (2x² + y) =


Odpowiedź :

a) = 5x + y

b) = 6x + 6 + 3x - 3 = 9x + 3

c) = 6x + 1 - 3x + 3 = 3x + 4

d) = x^2 + 16

e) = 6x^2 + 9xy - 6y^2 - 4xy

f) = x^2 - 5x - 25 + 5x = x^2 - 25

g) = 2x^3 - 6x^2y - 3y^2 + xy

Odpowiedź:

a) 5x+y =

b) 9x+3 =

c) 3x+3=

d) x'2+16=

e) 6x+y=

f) nie wiem

g)3x'2-2y=

'2. to kwadrat

nie wiem czy dobrze